Genotyping analysis of the Pax9 Gene in patients with maxillary canine impaction [version 1; peer review: 2 approved] - Evy Eida Vitria (F1000Research, 2019)
Background: Paired-box gene 9 (PAX9) mutation is potentially associated with impaction in some patient populations. Here, we analyzed the relationship between PAX9 polymorphism and the occurrence of maxillary canine impaction. Methods: Patients with and without maxillary canine impaction were selected based on specific inclusion criteria, and samples of genomic DNA were obtained from a buccal mucosa swab. DNA was amplified by polymerase chain reaction and sequenced for further bioinformatics analysis to identify single nucleotide polymorphism (SNP) genotypes. Genotype and allele counting was performed in both case and control groups prior to conducting statistical analysis. Results: Four SNPs were identified in patients with maxillary canine impaction, with relative confidence determined based on chromatogram-peak assessment. All SNPs were located in exon 3 of PAX9 and in the region sequenced by the primer pair −197Fex3 and +28Rex3. Three of the SNPs (rs375436662, rs12881240, and rs4904210) were reported previously and are annotated in NCBI (dbSNP version 150), whereas another SNP mapped to chromosome 14 has not been reported. Patients with a CC genotype at SNP 3 [odds ratio (OR): 2.61 vs. TT; 1.28 vs. CT] and a CC genotype at SNP 4 [OR: 0.71 vs. GG; 0.79 vs. CG] were more likely to have maxillary canine impaction. Conclusions: These results demonstrated that the presence of SNPs 3 and 4 is associated with increased likelihood of suffering from maxillary canine impaction.